The effect of regular exercise on menstrual cycle pattern and early follicular hormonal and physiolgical parameters in Turkish sportswomen - Ozmerdivenli, R.; Kumru, S.; Karacabey, K.; Gundogdu, C.; Saygin, O. (Inst Sport, 2007)
Objective The aim of this study was to establish the effects and duration of regular exercise on the menstrual pattern and the early follicular hormonal parameters in young sportswomen. Methods: The study included a total of 94 female students from the Firat University made up of 30 sedentary living, 32 involved in active sports for equal or less than 5 years and another 32 involved in sports for over 5 years. Group I was composed of 30 girls while Group 2 and Group 3 each containing 32 sportswomen involved in active sports for equal or less than 5 years and over 5 years, respectively. Results: The levels of (free)fT(3), fT(4), fT(3), fT(4), TSH, PRL, follicle stimulating hormone (FSH) and Luteinizing hormone (FSH) levels in the sera of the subjects were determined by the chemiluminiscence. The thyroid stimulating hormone values of the subjects was found to be higher in the sedentary group than that in the sportswomen groups, while the PRL, (totally) tT(3) and tT(4) levels was below that in both sportswomen groups. The difference was statistically significant (p < 0.01). Conclusions: We concluded that whereas regular but moderate level exercise does not affect serum gonadotropin and free thyroid hormone levels, and don't cause a disturbance on menstrual cycle pattern, it may lead an increase in serum PRL and total thyroid hormone levels.
Keywords: exercise; menstruation; hormone and sportswomen